Long-term data analyses and modelling of harbour porpoise distribution in the alpha ventus test site area as input to decision support tools for marine spatial planning : final report of the project: Accompanying ecological research at the alpha ventus offshore test site for the evaluation of BSH standard for environmental impact assessment (StUKplus) : [project duration: 01.01.2013 - 30.09.2013] ... : StUKplus final report "Long-term analyses harbour porpoises" ... - DHI-WASY GmbH, Berlin (Technische Informationsbibliothek (TIB), 2014)
Illustrationen, graphische Darstellungen, Karten ...